2001
DOI: 10.1128/aem.67.9.4036-4040.2001
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Fecal Coliforms in Dry-Composting Toilets

Abstract: The dry-composting toilet, which uses neither water nor sewage infrastructure, is a practical solution in areas with inadequate sewage disposal and where water is limited. These systems are becoming increasingly popular and are promoted to sanitize human excreta and to recycle them into fertilizer for nonedible plants, yet there are few data on the safety of this technology. This study analyzed fecal coliform reduction in approximately 90 prefabricated, dry-composting toilets (Sistema Integral de Reciclamiento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 4 publications
3
32
0
Order By: Relevance
“…13 These findings indicated that due to the hot, dry climate of the Chihuahuan desert, composting by biodegradation was not effective due to a rapid desiccation. As a result, after six months treatment of biowaste, only 36% of composting toilets produced United States Environmental Protection Agency (USEPA) Class A compost based on fecal coliform counts (< 1,000 most probable number fecal coliforms/gram).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…13 These findings indicated that due to the hot, dry climate of the Chihuahuan desert, composting by biodegradation was not effective due to a rapid desiccation. As a result, after six months treatment of biowaste, only 36% of composting toilets produced United States Environmental Protection Agency (USEPA) Class A compost based on fecal coliform counts (< 1,000 most probable number fecal coliforms/gram).…”
Section: Introductionmentioning
confidence: 91%
“…A previous study analyzed these ecologic systems for their ability to re-duce fecal coliforms and found a significant reduction over time. 13 A simple random sample of 90 households using SIRDOs in these three communities was selected. Complete data were available for 77 of this sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors (Gaspard and Schwartzbrod 2003;Cofie et al 2006;Koné et al 2007;El Fels et al 2014b) showed that the rise of temperature during the thermopilic stage leads to hygeinization. Furthermore, Redlinger et al (2001); Pietronave et al (2004) and Bhatia et al (2013) noted that a significant decrease of faecal coliforms and faecal Streptococci during composting. Paniel et al (2010) demonstrated that faecal Enterococcus was not observed during the stabilization phase.…”
Section: Coliforms Versus Time Of Co-composting Processmentioning
confidence: 99%
“…Most published work has used enterococci and thermotolerant coliforms as faecal contamination indicator organisms (Redlinger et al 2001). Their presence indicates poor hygiene.…”
Section: Coliforms Versus Time Of Co-composting Processmentioning
confidence: 99%